A Survey of Female Heroism in Jewish Tradition - HODOSSY-TAKÁCS, Előd (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Did warrior heroines exist in the Hebrew tradition? The answer is a seemingly reassuring yes, but the paper shows that the topos of female heroism was not a popular theme in Jewish tradition. To imagine ancient war scenes according to depictions in modern media can be misleading; the central purpose of this brief survey is to give a glimpse into this topic.